Inflation in New Zealand - Blyth, Conrad Alexander (Hornsby, N.S.W. : George Allen & Unwin Australia in association with N.Z. Institute of Economic Research, 1977)
This book describes and explains New Zealand's experiences and although it is primarily for New Zealanders it is a contribution to the understanding of inflation in all countries.
Aus
Distributed in New Zealand by Book Reps, Auckland.
Bibliography: p. 94-96.
osa; 26/07/18
Loans
Keywords: Inflation (Finance); Wage-price policy; New Zealand